Biomimetic toughening design of 3D-printed polymeric structures: Enhancing toughness through sacrificial bonds and hidden lengths - Zhiyuan Xu; Ran Tao; Kunal Masania; Sofia Teixeira de Freitas (Materials & Design)
Spider silk is known for its excellent strength and fracture resistance properties due to its molecular design structure, characterized by sacrificial bonds and hidden lengths. These structures have inspired reinforcements of synthetic polymer materials to enhance toughness. In this study, we mimic these natural toughening mechanisms by designing and manufacturing 3D-printed polymeric structures incorporating overlapping curls consisting of coiling fiber with sacrificial bonds and hidden lengths. Utilizing the liquid rope coiling effect, we manufactured overlapping curls using three polymers: polylactic acid (PLA), liquid crystal polymer (LCP), and polyamide 6 (PA6). Uniaxial tensile tests were performed to characterize the mechanical properties of overlapping curl as a function of geometries, post-treatments, and material constitutive parameters. Our results show that single-sided overlapping curls can fully unfold while double-sided curls are prone to premature failure. Heat-pressure post-treatment was found to significantly increase the load-capacity of the sacrificial bonds by up to Image 1 due to increased contact area. However, the defects introduced in the fibre after the break of the sacrificial bonds, make the structure more susceptible to premature failure, limit the complete unfolding of the hidden length, and lead to a decrease up to Image 2 of the toughness. To guarantee the complete unfolding of the hidden lengths and improve the toughness, we demonstrate that selecting a polymer material with either high fracture strength (e.g., LCP, Image 3) or high fracture strain (e.g., PA6, >2) is crucial, and increase toughness up to Image 4 and Image 5, respectively.